Comorbidity and survival after admission to the intensive care unit: A population-based study of 41, 230 patients. (May 2021) - Simpson, Alasdair; Puxty, Kathryn; McLoone, Philip; Quasim, Tara; Sloan, Billy; Morrison, David S
Purpose: To describe the relationship between comorbidities and survival following admission to the intensive care unit. Methods: Retrospective observational study using several linked routinely collected databases from 16 general intensive care units between 2002 and 2011. Comorbidities identified from hospitalisation in the five years prior to intensive care unit admission. Odds ratios for survival in intensive care unit, hospital and at 30 days, 180 days and 12 months after intensive care unit admission derived from multiple logistic regression models. Results: There were 41, 230 admissions to intensive care units between 2002 and 2011. Forty-one percent had at least one comorbidity – 24% had one, 17% had more than one. Patients with comorbidities were significantly older, had higher Acute Physiology and Chronic Health Evaluation II scores and were more likely to have received elective rather than emergency surgery compared with those without comorbidities. After excluding elective hospitalisations, intensive care unit and hospital mortality for the cohort were 24% and 29%, respectively. Asthma (odds ratio 0.79, 95% confidence interval 0.63–0.99) and solid tumours (odds ratio 0.74, 0.67–0.83) were associated with lower odds of intensive care unit mortality than no comorbidity. Intensive care unit mortality was raised for liver disease (odds ratio 2.98, 2.43–3.65), cirrhosis (odds ratio 2.61, 1.9–3.61), haematological malignancy (odds ratio 2.29, 1.85–2.83), chronic ischaemic heart disease (odds ratio 1.53, 1.19–1.98), heart failure (odds ratio 1.79, 1.35–2.39) and rheumatological disease (odds ratio 1.53, 1.18–1.98). Conclusions: Comorbidities affect two-fifths of intensive care unit admission and have highly variable effects on subsequent outcomes. Information on the differential effects of comorbidities will be helpful in making better decisions about intensive care unit support and understanding outcomes beyond surviving intensive care unit.